A new North American genus of Hetaeriinae (Coleoptera: Histeridae), with descriptions of six new species from the U.S.A. and Mexico - Tishechkin, Alexey K.; Caterino, Michael S. (Zootaxa, 2009)
Renclasea n. gen., a genus of the Hetaeriinae (Histeridae), with six species, R. skelleyi n. sp. (United States: Florida and Georgia), R. falli n. sp. (United States: California), R. helavai n. sp. (United States: Arizona), R. mexicana n. sp. (Mexico: Hidalgo), R. occidentalis n. sp. (United States: Arizona and New Mexico) and R. cazieri n. sp. (United States: Arizona), are described, illustrated and diagnosed. The status of two female specimens of Renclasea from western Texas, apparently closely related to R. occidentalis, remains uncertain. The only host record available for the genus is an association of R. mexicana with undetermined species of Neivamyrmex army ants.